A Determination of Topics for Health Technology Assessment in Thailand: Case Study of Decision Makers Participation - Lertpitakpong, Chanida; Chaikledkaew, Usa; Thavorncharoensap, Montarat; Tantivess, Sripen; Praditsitthikorn, Naiyana; Youngkong, Sitaporn; Yothasamut, Jomkwan; Udomsuk, Kanchanart; Sinthitichai, Kongkoch; Teerawattananon, Yot (Journal of Health Science of Thailand, 2017)
This study was to describe experiences and findings from the topic selection process for health technology assessment (HTA) conducted by Health Intervention and Technology Assessment Program. The process comprised of 5 stages namely: 1) determining objectives, scope and involved stakeholders; 2) requesting potential topics for assessment from decision makers at the national health authorities; 3) reviewing related literature on and prioritizing the proposed HTA topics by HITAP researchers; 4) selecting the HTA topics by decision makers; 5) analyzing the strengths and weaknesses of the current topic selection processes by HITAP staff. The strengths of the topic selection were systematic and transparent. It also required participation from stakeholders; however, the limitations were topics prioritization methods and time constraints. Lessons learnt from this procedure can be useful for improving the next HTA topic selection in order to increase the usefulness of the future HTA results. It was recommended that numbers of selected topics for the final selection process should be reduced in order to extend allotted time for presentations and discussion among decision makers (in step # 4). Furthermore, topic prioritization methods should be agreed among participants. This consequently makes results of the topic prioritization being accepted and also reduce biases which might arise during prioritizing process. Additionally, involved parties would be expanded and prioritized topics should be publicized. This is to reduce duplication of HTA studies, and to guide those who are interested in conducting HTA particularly on critical national health issues.